Identifikasi Pengetahuan Tradisional Masyarakat Sentani dan Peluangnya untuk Pembelajaran Fisika - Triwiyono Triwiyono; Sudardja Adiwikarta (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research is aimed to investigate, to describe and to elaborate the system of traditional knowledge of Sentani society in Papua. Research method is qualitative. The conduction of the research has been done in forms of interview, field observation, and bibliography study that to spent four months. Respondents were chosen purposively. Some findings on traditional knowledge that related to physics are about ethnophysics, and transportation. The most important finding is that the traditional knowledge has not been able to explain all natural phenomena, moreover scientifically. For example solar-eclipse, lightning as an incredible mystical phenomena.